REVENGE TOURISM: ANALISIS MINAT WISATAWAN PASCA PANDEMI COVID-19 - Annisa Aulya Sudjana; Siti Nur Aini; Hilman Khaerul Nizar (Pringgitan, 2021)
This study aims to determine the interest of tourists after the Covid-19 pandemic related to the trend of "Revenge Tourism" or what is interpreted as revenge to travel after the Covid-19 pandemic. Apart from being able to know the interest of tourists from this research, it can also be known the type of tourism, budget, length of stay and other aspects of tourists that can be used as knowledge for tourism actors to make mitigation in tourist destinations to anticipate tourist surges and to help re-storing Indonesian tourism after the pandemic. The research method used is descriptive quantitative research, collecting data using a questionnaire consisting of 3 parts of questions, about tourist demographics, questions using the AIDA scale (Attention, Interest. Desire, and Action), the last part of the questionnaire includes budget, length of stay, and top 3 destinations. The test subjects are people who are scattered in various provinces in Indonesia, and are limited to collecting a sample of at least 100 respondents. The sampling technique used was random sampling technique and data processing was done quantitatively using the SPSS application. The data is presented in the form of a diagram that represents the presentation of processed data. The results obtained were that the 3 most wanted destinations to be visited after the pandemic were DI Yogyakarta, Labuan Bajo and Bali. And the types of marine tourism, mountain nature tourism and culinary tourism are the types of tourism that are most in demand by tourists. The budget prepared by tourists for post-pandemic travel is in the range of 1-3 million rupiah and the time for traveling is 3-4 days.Keywords: Revenge Tourism, Travel intention, AIDA Scale